Bully - Hirsch, Lee (Beverly Hills, CA : Anchor Bay Entertainment, 2013)
This is a character-driven documentary following five kids and families over the course of a school year. Offering insight into different facets of America's bullying crisis, the stories include two families who have lost children to suicide and a mother awaiting the fate of her 14-year-old daughter, who has been incarcerated after bringing a gun on her school bus. Documentary provides an intimate and often shocking glimpse into homes, classrooms, cafeterias and principals' offices.
MPAA rating: PG-13; for "intense thematic material, disturbing content, and some strong language--all involving kids"--Container.
In English with optional Spanish ; closed-captioned for the hearing impaired.
Keywords: Bullying -- United States; Bullying in schools -- United States; Bullying -- Prevention